Historical aspects and current view for device-based endometrial destruction - Sergey P. Sinchikhin; Ekaterina V. Kostenko; Lusine V. Stepanyan; Ekaterina S. Sinchikhina (IP Berlin A.V., 2023)
A historical perspective on the issue of device-based endometrial destruction is presented. The article describes in detail various current methods of thermal coagulation of the uterine mucosa for its destruction. A comparative analysis of hysteroscopic and non-hysteroscopic methods of endometrial destruction in terms of treatment effectiveness, complications, and recurrence prevention is presented. The ways of technological development of instrumental treatment methods of intrauterine disorders are highlighted.